PENERAPAN COGNITIVE BEHAVIOR THERAPY BERBASIS ISLAM BAGI PECANDU ALKOHOL - Fahrurrazi Fahrurrazi; Nurjannah Nurjannah (JIVA : Journal of Behavior and Mental Health, 2021)
ABSTRACTTherapy for alcoholics with the use of cognitive behavior-based Islam shows the results of a progressive. This study aims to obtain a comprehensive overview of the application of cognitive behavior therapy-based Islam in helping individuals overcome alcohol addiction. This study uses a qualitative research method is phenomenological. Participant research is an alcoholic. Data collection was performed by the method of triangulation, namely in-depth interviews (depth interviews) face to face with the observation and scale. Procedure the study was conducted with three step, namely the preparatory stage of the study, the implementation phase of the research, and the last stage of the evaluation of the results of the research. As for the results of the study showed that the application of cognitive behavior therapy-based Islam on individuals who experience addiction to alcohol showed significant changes in cognition, emotions and behavior of participants. Through the technique of cognitive restructuring, cognition participants who distorted changed to be more rational. Participants are able to set a good lifestyle, independent in work, respect people around and back to the right path in accordance with the teachings of Islam. a change in cognition in participants encourage the reduction behavior of consuming alcohol.Keywords: Cognitive behavior therapy-based Islami; alcoholicsÂ ABSTRAKTerapi bagi pecandu alkohol dengan menggunakan cognitive behavior therapy berbasis Islam menunjukkan hasil yang progresif. Penelitian ini bertujuan untuk mendapatkan gambaran menyeluruh dari penerapan cognitive behavior therapy berbasis Islam dalam membantu individu mengatasi kecanduan alkohol. Penelitian ini menggunakan metode penelitian kualitatif bersifat fenomenologis. Partisipan penelitian adalah seorang pecandu alkohol. Pengumpulan data dilakukan dengan metode triangulasi yakni wawancara mendalam (depth interview) secara face to face dengan observasi dan skala. Prosedur penelitian dilakukan dengan tiga tahap, yaitu tahap persiapan penelitian, tahap pelaksanaan penelitian, dan terakhir tahap evaluasi hasil penelitian. Adapun hasil penelitian menunjukkan bahwa penerapan cognitive behavior therapy berbasis Islam pada individu yang mengalami kecanduan alkohol menunjukkan perubahan yang signifikan pada kognisi, emosi dan perilaku partisipan. Melalui teknik cognitive restructuring, kognisi partisipan yang terdistorsi berubah menjadi lebih rasional. Partisipan mampu mengatur pola hidup yang baik, mandiri dalam bekerja, menghormati orang di sekitarnya dan kembali ke jalan yang benar sesuai dengan ajaran Islam. adanya perubahan kognisi pada partisipan mendorong berkurangnya perilaku mengkonsumsi alkohol.Kata kunci: Cognitive behavior therapy berbasis Islami; Pecandu alkohol